Children's television in India : a situational analysis - Karnik, Kiran S. 1942-; Lal, C.; Vishwanath, K. (New Delhi : Concept Pub. Co., 1999)
A set of recommendations to improve the quality of children's television in India.
Includes bibliographical references (p. [77]-79) and index.
Keywords: Children's television programs -- India; Television and children -- India; Television in education -- India